2014
DOI: 10.1007/s11663-014-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved CFD Model to Predict Flow and Temperature Distributions in a Blast Furnace Hearth

Abstract: The campaign life of a blast furnace is limited by the erosion of hearth refractories. Flow and temperature distributions of the liquid iron have a significant influence on the erosion mechanism. In this work, an improved three-dimensional computational fluid dynamics model is developed to simulate the flow and heat transfer phenomena in the hearth of BlueScope's Port Kembla No. 5 Blast Furnace. Model improvements feature more justified input parameters in turbulence modeling, buoyancy modeling, wall boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…This has mainly been done based on continuum models. [19,21,23,26,27,[83][84][85][86][87][88][89][90] Generally, these models consider a single-phase flow, treat the coke bed as porous media, neglect movements of coke and liquid interface, and regard the flow and heat transfer as under a steady state. Also, Finite Volume Method (FVM), which is widely used in CFD computation, was Figure 2.…”
Section: Flow and Heat Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…This has mainly been done based on continuum models. [19,21,23,26,27,[83][84][85][86][87][88][89][90] Generally, these models consider a single-phase flow, treat the coke bed as porous media, neglect movements of coke and liquid interface, and regard the flow and heat transfer as under a steady state. Also, Finite Volume Method (FVM), which is widely used in CFD computation, was Figure 2.…”
Section: Flow and Heat Transfermentioning
confidence: 99%
“…Comparison of the calculated and measured temperatures for Cases A-D): cross dots, measured temperature; dashed lines, calculated temperature for the coke bed with the porosity of 0.35 and the particle size of 30 mm; and solid lines, calculated temperature for the bed coke with the porosity of 0.30 and the particle size of 12 mm. [27] Figure 4. It reveals that the floating state of the coke bed becomes more obvious in the hearth with increasing gas velocities.…”
Section: Discrete Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…1) The performances of carbon brick in blast furnace hearth have been widely studied. [1][2][3][4][5][6][7][8][9][10][11][12] These studies indicated that the peripheral flow of molten iron, dissolution of molten iron, attack of zinc and alkalis, thermal stress and fluid induced shear stress are the reasons for the corrosion of carbon brick. With the deterioration of raw materials and fuels, the blast furnace is facing great challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Successful formation of a protection layer near the eroded regions of the hearth refractory lining depends greatly on the flow and heat transfer of the liquid iron and hence furnace operating conditions. The flow and heat transfer in the hearth is quite complex itself . Further, the dosage of titania required to form the protection layer should be minimized as excess amounts cause adverse effects on the post‐processing of liquid iron.…”
Section: Introductionmentioning
confidence: 99%